Efficiency in Human Resource Management through the Digital System “Satu Kemenkeu”: An Evaluation of Automation within the Ministry of Finance in Indonesia - Erwin, E.; Riau, Dwi Putranto; Akadira, Tora (Manunggal Halim Jaya, 2025)
This study aims to evaluate the effectiveness of the digital automation system